2020
DOI: 10.1080/02673843.2020.1728560
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the preventive intention on premarital sexual behaviours among junior high school students in lower-northern region of Thailand

Abstract: This study investigated factors affecting the preventive intention on premarital sexual behaviours among junior high school students in lowernorthern region of Thailand. A cross-sessional study was conducted. Stepwise regression model was used to run multiple linear regression. Self-awareness was the best predictor of the preventive intention on premarital sexual behaviours for having the biggest coefficient (Beta coefficient equal to 0.696, t = 19.183, P = 0.001). Self-awareness had positive and significant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The findings of this study are consistent with previous research about the factors affecting product infringements of Chiang Mai's teenage consumers. This research showed how different cultural, social, and psychological factors changed product consumption patterns (12).…”
Section: Discussionmentioning
confidence: 87%
“…The findings of this study are consistent with previous research about the factors affecting product infringements of Chiang Mai's teenage consumers. This research showed how different cultural, social, and psychological factors changed product consumption patterns (12).…”
Section: Discussionmentioning
confidence: 87%